Role of The Head of School In The Formation of Islamic-Based School Culture (Case Studi in SMP Muhammadiyah 30 Sihepeng Kab. Mandailing Natal) - Mukhlis (PT. Willy Print Art, 2024)
The Islamic-based school culture in SMP Muhammadiyah 30 Sihepeng consists of religious activities and internalization of values ​​as well as existing symbols such as vision and mission and motto. The religious activity is in the form of routine activities, namely in the morning before the lesson the researcher sees the children praying before starting the lesson. The strategy for the formation of Islamic-based school culture can be in the form of power strategy, persuasive strategy and normative re educative. The Islamic-based school culture formation model used is the organic model. The organic model, namely the creation of an Islamic-based school culture that is encouraged by the view that Islamic religious education is a unit or as a system (consisting of complex components) that seeks to develop a religious outlook / spirit of life, manifested in life attitudes and life skills Islamic. The principal can take a role in shaping an Islamic-based school culture by playing the role of educator, manager, leader, supervisor and innovator. These five roles can be used to shape Islamic-based school culture